Carbon calculator tracks the climate benefits of managed private forests - W Stewart; B Sharma (California Agriculture, 2015)
As part of California's strategy to reduce greenhouse gas emissions, private forest landowners are now required to address carbon sequestration as a management goal when submitting timber harvest plans. Using public data on forests and forest products, we developed a calculator that tracks the carbon sequestration benefits related to live trees, wood used for bioenergy and wood going into products. The calculator is adapted for different forest types, forest management techniques and time frames. Based on current best practices used in California, we estimate that harvested and regenerated forests will provide approximately 30% more total carbon sequestration benefits than forests left to grow for an equal time. More than half of the total benefits relate to harvested wood substituting for fossil fuels and fossil fuel–intensive materials such as cement and steel. With relatively efficient management practices, harvesting a ton of wood provides more sequestration benefits than leaving that ton growing in the forest.